The effect of low-grade intraventricular hemorrhage on neurodevelopment of very low birth weight infants - Yaghini, Omid; Majidinezhad, Maede; Ghehsareh Ardestani , Azam; Riahinezhad, Maryam; Maracy, Mohammad Reza (Iranian Journal of Child Neurology, 2022)
Objective Intraventricular hemorrhage (IVH) is a significant concern for premature very low birth weight (VLBW) neonates worldwide. Recently, the popular theory of the benign nature of low-grade IVH has been argued with uncertain outcomes. This study has aimed to assess the effect of low-grade IVH on neurodevelopment of VLBW neonates. Materials & methods This was a six-month follow-up cohort study conducted on VLBW neonates with and without grade I-II IVH diagnosed through brain ultrasonography. The participants were neurologically examined at birth and within six months. Their neurodevelopment was assessed using Bayley-III questionnaire evaluating cognition, receptive language, expressive language, fine motor and gross motor performance. Results 100 VLBW neonates including 40 cases with grade I-II IVH diagnosed through brain ultrasonography and 60 controls were recruited. The cases and controls were similar considering gestational age, body birth weight, hospitalization duration, gender distribution and age at Bayley-III evaluation (P>0.05). The neurological assessments at birth showed no significant difference between the two groups (P=0.20), while controls were significantly showed better results in the sixth month of age (P =0.004). Assessing different neurodevelopmental indices, after controlling for demographic characteristics and respiratory-related variables at the time of Bayley-III evaluation, There was a higher performance in cognition and gross motor aspects in controls compared with cases (P= 0.04 and 0.03, respectively). Conclusions The low-grade IVH affected the sixth-month neurological examination and gross motor performance of the VLBW newborns. Notably, cognition and gross motor were the two affected subscales in the presence of low-grade IVH, independent of demographic factors.